Asymmetric effect of oil price changes on trade balance in Saudi Arabia, Kuwait and United Arab Emirates - Muhammad, Faheem; Mohamed, Azali; Lee, Chin; Mazlan, Nur Syazwani (Johar Education Society Pakistan, 2020)
The fluctuations in oil price have vital importance for their presumed role in the trade balance. Our study investigates the oil price fluctuation effect on the trade balance for period 1980-2017. We employ linear and nonlinear autoregressive distributed lag models simultaneously and find the heterogeneous response of Saudi Arabia, Kuwait and United Arab Emirates to oil price fluctuations. The nonlinear ARDL results indicate oil price affects trade balance asymmetrically. We also analyze the moderating effect of real effective exchange rate on the oil-trade balance relationship that found an adverse impact in Saudi Arabia and Kuwait while the positive impact in case of United Arab Emirates trade balance. The oil price marginal effect evaluated at the minimum level of the real effective exchange rate is positive in Kuwait and negative in Saudi Arabia and United Arab Emirates. It also shows positive at the maximum level of the real effective exchange rate in Kuwait and United Arab Emirates while negative in the case of Saudi Arabia that varies at different levels of exchange rate. The findings of the study give policy recommendation related to positive and negative changes of oil price that appear to have a valuable impact on economic decisions.